Testing the Equality of the Means of Two Populations with Unequal Variances - W.Y, Pan,; A.H, Pooi, (Malaysian Journal of Science, 2007)
The Behrens-Fisher problem is the problem of comparing the means when the assumption of normality for the distributions is made and the variances are different. A widely used solution to this problem is Welch's test. Presently an alternative test is proposed. The alternative test is found to be comparable to Welch's test in tenns of Type-I and Type-II errors.